Review on fly ash-based geopolymer concrete without Portland Cement - Mohd Mustafa, Al Bakri; Mohammed, H.; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr.; Khairul Nizar, Ismail, Prof. Madya Dr.; Zarina, Yahya (Academic Journals, 2011)
Link to publisher's homepage at http:// www.academicjournals.org/